Nursing students’ perceptions about the use of clinical simulation to teach safe medication administration: a focus group study - Cristina Alfonso-Arias; Mireia Llaurado-Serra; Encarna Rodríguez-Higueras; Blanca Goni-Fuste; Laura Brichs-Masnou; Laia Wennberg-Capellades; Maria Angeles de Juan-Pardo (BMC Nursing)
Abstract Background Safe medication administration is a core competence that nursing students need to acquire during their training. Clinical simulation facilitates the integration of theoretical and practical knowledge in a safe environment, facilitating engagement and greater confidence. However, it is important to integrate students’ perceptions to optimize their learning experience to achieve the desired learning outcomes. The purpose of this study was to explore nursing students’ perceptions about the use of clinical simulation to teach safe medication administration. Methods Descriptive qualitative study through focus groups with nursing students who had participated in simulation-based training on safe medication administration where they had been split into two groups that differed only on the degree of fidelity (low fidelity mannequin or standardized patient). Four focus groups were conducted with 24 nursing students who had participated in simulation-based training on safe medication administration. Group discussions were transcribed and subjected to thematic analysis. Results Two themes with four subthemes emerged. Theme (1) Usefulness of the clinical simulation for acquiring competence in safe medication administration; included three subthemes. Students reported that simulation-based training helped them link theory and practice, increasing self-awareness of their medication competence and highlighting the importance of training in safe medication administration. Theme (2) “Elements of simulation design that foster learning”; included one subtheme. Students highlighted that having to work individually heightened their sense of responsibility and enabled them to identify their current strengths and weaknesses. The opportunity to observe classmates was seen as useful for learning from mistakes. Conclusions The results of this study support the use of clinical simulation to teach nursing students the process of safe medication administration, although it is important that learning scenarios are adapted to students’ level of experience and competence.